Does prenylation predict progression in NAFLD?. Issue 3 (27th December 2018) - Ghorbani, Peyman; Smith, Tyler KT; Fullerton, Morgan D
Abstract: Non‐alcoholic fatty liver disease (NAFLD) often develops in concert with related metabolic diseases, such as obesity, dyslipidemia and insulin resistance. Prolonged lipid accumulation and inflammation can progress to non‐alcoholic steatohepatitis (NASH). Although factors associated with the development of NAFLD are known, triggers for the progression of NAFLD to NASH are poorly understood. Recent findings published in The Journal of Pathology reveal the possible regulation of NASH progression by metabolites of the mevalonate pathway. Mevalonate can be converted into the isoprenoids farnesyldiphosphate (FPP) and geranylgeranyl diphosphate (GGPP). GGPP synthase (GGPPS), the enzyme that converts FPP to GGPP, is dysregulated in humans and mice during NASH. Both FPP and GGPP can be conjugated to proteins through prenylation, modifying protein function and localization. Deletion or knockdown of GGPPS favors FPP prenylation (farnesylation) and augments the function of liver kinase B1, an upstream kinase of AMP‐activated protein kinase (AMPK). Despite increased AMPK activation, livers in Ggpps ‐deficient mice on a high‐fat diet poorly oxidize lipids due to mitochondrial dysfunction. Although work from Liu et al provides evidence as to the potential importance of the prenylation portion of the mevalonate pathway during NAFLD, future studies are necessary to fully grasp any therapeutic or diagnostic potential. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.